Depression and anxiety have unique contributions to somatic complaints in depression, irritable bowel syndrome and inflammatory bowel diseases - SAKALLI KANİ, AYŞE; KANİ, HALUK TARIK; SAYAR, MUSTAFA KEMAL; YANARTAŞ, ÖMER; ATUĞ, ÖZLEN; ERGÜN, SERHAT (TAYLOR & FRANCIS LTD, 2019)
OBJECTIVE: In this study we aim to investigate the effects of somatic and related symptoms (SARS), alexithymia, hypochondriasis, anxiety and depression on patients with major depressive disorder, irritable bowel syndrome, inflammatory bowel disease which are the representative diseases of brain gut axis (BGA). METHOD: Sex and age similar groups of participants with major depressive disorder (MDD) (n = 102), irritable bowel syndrome (IBS) (n = 51), inflammatory bowel diseases (IBDs) (n = 54), and control group (n = 67) were included into this study. Depression and IBS were diagnosed according to DSM-5 and ROME 4 criteria, respectively. IBDs were established according to endoscopic, histological, and radiographic investigations. In all participants, somatic and related symptoms were evaluated by self-report scales including Bradford Somatic Inventory (BSI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Whiteley Index (WI), The 20-item Toronto Alexithymia Scale (TAS-20), Somatosensory Amplification Scale (SAS). RESULTS: BSI, BDI, BAI, WI, TAS-20 and SAS scores were found to be highest in patients with MDD; scores of patients with IBS and IBDs were similar but higher than the control group. Gastrointestinal somatic symptoms including nausea, stomach burning, abdominal ache and stomach swelling were observed in more than half of the patients with MDD. The most common extra-intestinal somatic symptoms were, headache and neck pain and/or tension, and leg pain in IBS patients. However leg pain, weakness and lack of energy, and neck pain/tension were highest in IBDs patients. While the strongest correlation determined was between the BSI and anxiety scores in MDD (p<.001, r = .688) and IBS group; (p<.001, r = .51), in IBDs patients, BSI scores were more significantly correlated with depressive scores instead of anxiety (p<.001, r = .712 vs. r = .705, p<.001). CONCLUSION: Our study demonstrates that SARS are commonly observed in the representative diseases of BGA. Extra-intestinal somatic symptoms are common in IBS, and IBDs, and also gastrointestinal somatic symptoms are common in patients with MDD. Assessment of somatic and related symptoms is quite important in the context of BGA.
Keywords: Depression; anxiety; somatic symptoms; brain gut axis; inflammatory bowel diseases; irritable bowel syndrome; FUNCTIONAL GASTROINTESTINAL DISORDERS; TORONTO-ALEXITHYMIA-SCALE; PRIMARY-CARE; SYMPTOMS; INVENTORY; SOMATIZATION; AMPLIFICATION; RELIABILITY; PREVALENCE; MANAGEMENT